Las lesiones de tronco de coronaria izquierda: ¿Cirugía o intervencionismo?. - ASTE SALAZAR, Hernán (Revista Médica Herediana, 2013)
In recent years there has been some improvement in surgical and interventional techniques that have modified the classical indications making them more risky. Left main coronary stenoses are even more dreadful lesions, and the results of percutaneous management are odd with varying mortality (10-12% on average), and high morbidity. Moreover we have small number of cases in the literature. Comparing these results with surgery, we find the later to be safer with mortality under 4%, low morbidity and a long term experience in the management of this pathology. Results, moreover, tend to favor surgery in the coronary restenosis in spite of the use of stents. ( Rev Med Hered 2003; 14: 204-206).